Introduction of the Minimum Tax in Slovenia and Croatia - Blažič, Anita (The Journal of Accounting and Management, 2025)
In the past decade, multinational companies have exploited differences in tax systems between countries to reduce their tax liabilities. In response, the OECD, in collaboration with the G20, has established a global minimum tax agreement to ensure fairer taxation and reduce base erosion and profit shifting. This measure promotes transparency, reduces profit transfers to tax havens, and encourages responsible tax policies. Both Slovenia and Croatia have joined the global minimum tax agreement and have started implementing measures to comply with new international standards aimed at preventing tax avoidance through the use of tax havens. The introduction of the minimum tax is a significant step in combating tax evasion and improving global tax fairness, which will benefit both countries and the global economy in the long term.